The potential of Cow's paw (Bauhinia forficata) as a food and therapeutic alternative: a scientific investigation - SILVA, Tatiane Jardim da (130, 2024)
Bauhinia forficata, commonly known as cow's paw, is among the species most used for this purpose. Among the representatives of Bauhinia, the one with the largest number of studies regarding hypoglycemic and antidiabetic activity is the species mentioned. This is because, due to its pharmacological activities, several studies report its botanical aspects, chemical composition and effectiveness. This constant interest in itsstudy is imperative for its safe and effective use. Therefore, the objective of this work is to provide information botany of these plants, which constitute a importance for the differentiation of species aiming at their correct use. Furthermore, given the medicinal and ornamental of the genre, aspects will be covered extremely pertinent agronomic criteria, since these promote studies of propagation strategies for species and their cultivation; whether they are intended for urban afforestation or planting in areas outside crops medicinal products as “windbreaks”.

RESUMO: Bauhinia forficata, comumente conhecida como pata de vaca, está entre as espécies mais usado para esse fim. Dentre os representantes da Bauhinia, aquele com maior número de estudos sobre atividade hipoglicemiante e antidiabética é a espécie citada. Isso porque, devido às suas atividades farmacológicas, diversos estudos relatam seus aspectos botânicos, composição química e eficácia. Este interesse constante no seu estudo é imperativo para a sua utilização segura e eficaz. Portanto, o objetivo deste trabalho é fornecer informações botânicas dessas plantas, que constituem uma importância para a diferenciação de espécies visando seu correto uso. Além disso, dada a natureza medicinal e ornamental do gênero, serão abordados aspectos de critérios agronômicos extremamente pertinentes, uma vez que estes promovem estudos de estratégias de propagação de espécies e seu cultivo; sejam eles destinados à arborização urbana ou ao plantio em áreas fora de cultivos de medicamentos como “quebra-ventos”.
O potencial da Pata de vaca (Bauhinia forficata) como alternativa alimentar e terapêutica: uma investigação científica
Artigo científico válido como TCC. Publicado em: InternationalJournalofMultidisciplinaryResearchandExplorer(IJMRE) / VolumeNo.4, Issue.1, 2024 / https://doie.org/10.0409/IJMRE.2024586
Keywords: Plantas comestíveis; Alimentos não convencionais; Produção Alimentícia